Health Seeking Behavior of Infant: An Ethnographic Study of Farming Families in Kumbang Village, North Aceh - Sakinah, Sani (Jurnal Publikasi Kesehatan Masyarakat Indonesia, 2025)
Health-seeking behavior for infants is carried out by mothers, but decision-making related to this is influenced by their husbands or parents. This is also influenced by knowledge, attitudes, beliefs, traditions, and the ecological conditions of their place of residence. Infant health problems often arise in rural areas where the majority of the population are farmers, so this study can be used as preliminary data in the design of programs to eliminate infant problems in rural areas. This study explores infant health-seeking behavior in farming families in rural areas. An ethnographic approach was used with data collection techniques including in-depth interviews, participant observation, documentation, and secondary data. The interpretive paradigm focuses on the meaning of the farming community itself regarding various infant health problems that guide considerations for seeking health care for infants. Informants were selected using purposive sampling, with a total of 4 stakeholders and 10 people who care for infants in farming and non-farming families as a validity test. The results of this study indicate that farming families choose health-seeking behaviors in three practices, including self-medication with leaves for diseases commonly found in infants, medical treatment when common diseases do not heal or for diseases with severe symptoms that appear quickly, and traditional medicine (rajah) when self-medication and medical treatment are ineffective.